Plagiarism Detection Using Artificial Intelligence - Sadhin, Ismail Hossain; Hassan, Tanvir; Nayim, MD. Al Muzahid (International Journal of Computer and Information System (IJCIS), 2024)
Abstract—Presently available plagiarism detection technologies are primarily restricted to string-level comparisons between potentially original texts and suspiciously plagiarized materials. The objective of this research is to enhance the precision of plagiarism identification by integrating Natural Language Processing (NLP) methods into current methodologies. Our proposal is an external plagiarism detection framework that uses various natural language processing (NLP) approaches to examine a set of original and suspicious papers. The techniques not only analyze text strings but also the text's structure, taking text relations into consideration. Preliminary findings using a corpus of short paragraphs that have been plagiarized demonstrate that NLP approach increase the correctness of current methods.